Avaliação da locomoção de cães submetidos à ostectomia unilateral da cabeça e colo femorais - Conti, Juliano Bortolo De [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate dogs with unilateral femoral head and neck ostectomy through standard clinical evaluation and using a pressure-sensitive walkway. The hypothesis was that these dogs exhibit changes in kinetic and temporospatial parameters due to the surgical procedure that may detected by Symmetry Index (SI). Thirty dogs divided into two groups were used: G1 had 15 clinically healthy dogs; G2 had 15 dogs that underwent unilateral femoral head and neck ostectomy performed through access craniolateral and without muscle interposition. The velocity was maintained from 0.9-1.1 m/s and acceleration from -0.15 to 0.15 m/s2. Five valid trials were analyzed for each dog. The peak vertical force, vertical impulse, gait cycle time, stance time, swing time, stride length, and the percentage body weight distribution among the four limbs were determined. The Symmetry Index was calculated between limbs for each variable in G1 and G2. After this, Symmetry Indices were compared between Groups. Limb function (G2) was considered excellent in 10 dogs, good in four, and fair in one case. The operated limb was shortened and circumferential measurement of the thigh was lesser compared to contralateral limb. Hip extension was limited. In radiographic examination, displacement of the proximal femur was observed in all operated limbs. Statistical differences were observed for the Symmetry indices between G1 and G2 in several temporospatial parameters. Impulse was statistically different comparing SI of the G1 hind limb/forelimb with G2 operated hind limb/ipsilateral forelimb and G2 operated hind limb/diagonal forelimb. In conclusion, dogs with unilateral femoral head and neck ostectomy have changes mostly in temporospatial parameters that may be detected by SI, despite good functional results

O trabalho teve por objetivos avaliar cães submetidos à ostectomia unilateral da cabeça femoral, por meio de avaliação clínica padrão e locomovendo-se em plataforma de pressão. A hipótese é que esses animais tenham alterações cinéticas e têmporo-espaciais decorrentes do procedimento cirúrgico, que podem ser detectadas por índice de simetria. Foram utilizados 30 cães divididos em dois grupos equitativos: Grupo 1 - animais hígidos; Grupo 2 – animais submetidos à ostectomia unilateral da cabeça e colo femorais, por meio de acesso craniolateral e sem interposição muscular. A velocidade foi mantida entre 0,9 e 1,1 m/s e a aceleração entre -0,15 e 0,15 m/s2. Foram determinados o Pico de Força Vertical, Impulso Vertical, duração do ciclo de locomoção, duração da fase de apoio, duração da fase de balanço, comprimento do passo e porcentagem de distribuição de peso. O Índice de Simetria (IS) foi calculado entre os membros para cada variável dos grupos 1 e 2. Na sequência, os Índices de Simetrias foram comparados entre Grupos. O resultado funcional (Grupo 2) foi considerado excelente em 10 animais, bom em quatro e razoável em um caso. O membro operado estava encurtado e a medida da circunferência da coxa foi menor comparado ao membro contralateral. A extensão do quadril estava limitada. Ao exame radiográfico foi observado deslocamento proximal do fêmur em todos os membros operados. Diferenças estatisticamente significantes foram observadas para os Índices de Simetria entre G1 e G2 em diversos parâmetros têmporo-espaciais. O Impulso Vertical foi estatisticamente significativo comparando o IS de G1 membro pélvico/membro torácico com G2 membro pélvico operado/membro torácico ipsilateral e membro pélvico operado/membro torácico diagonal. Foi possível concluir que cães com ostectomia unilateral da cabeça e colo femorais apresentam mudanças principalmente nos parâmetros têmporo-espaciais, as quais ...
Keywords: Cão - Doenças; Femur - Cirurgia; Ossos - Cirurgia; Locomoção animal; Femur - Surgery